Is the process of graduation of least developed countries (LDCS) suitable and sufficient? - Navarro-Pabsdorf, Margarita; Cuenca-Garcia, Eduardo; Ramirez-Franco, Luz Dary; Sanchez-Andres, Antonio (Technological and Economic Development of Economy, 2025)
Millions of people are living in the Least Developed Countries (LDCs), the poorest of the poor. Getting them out of that situation is one of humanity’s most urgent tasks. Since 1971, the United Nations has recognized LDCs as a category of countries characterized by, among others, dependence on international trade, rapid population growth, low literacy, an unskilled labor force and poorly developed institutions. This research analyzes the patterns in the evolution of a group of LDCs that have led them to graduation. This paper assesses whether the established way to leave this group of countries is realistic and foundational for future progress. The paper is organized as follows: Section 1 is a brief introduction on LDCs and their characteristics, Section 2 presents the method applied to obtain the results, focusing on criteria that must be met; Section 3 provides the results for the countries in the graduation process; Section 4 includes a discussion and comments on the results; Section 5 summarizes the main findings and draws conclusions. Additionally, a bibliographical review of the literature consulted is provided.First published online 18 March 2025